Multinational Corporations and Local Firms in Emerging Economies - Hansen, Michael W.; Rugraff, Eric (EADI, 2011)
Globally, policymakers and scientists are increasingly recognizing that close direct and indirect interaction between multinationals and local businesses is essential if foreign investment is to have a profound, lasting positive effect on the host country. Nevertheless, the interaction between multinationals (MNCs) and local companies has received relatively little attention in the scientific literature. This book aims to contribute to this with a number of studies in development economies into the spillover and linkage effects of MNCs on local companies. In addition, it describes policy experiences of various countries in their attempt to promote closer interactions between MNCs and local businesses. This book focuses in particular on researchers in economics, business administration, international relations, political science, development and area studies. Policy makers in the development field can also draw inspiration from it.